Nalar dan Mistis dalam Al-Qur’an: Analisis Tafsir Al-Mizan Terhadap Surah Al-An’am (6:122) - Rudi Setiawan; Aulia Yudistina (Jurnal Studi Qur'an dan Tafsir, 2025)
This article analyzes Allamah Thabathaba'i's Al-Mizan commentary on Surah Al-An'am (6:122) with a focus on the interaction between reason and mysticism in the Qur'an. This research examines how Thabathaba'i interprets the concepts of life, death, light and darkness in a spiritual context, and how this interpretation combines rational and mystical approaches. The method used in this research is a literature study with a descriptive-analytical approach. The results of the study show that Al-Mizan's interpretation uses the tahlili method by connecting the verses of the Qur'an thematically. Thabathaba'i emphasizes that true life is not only physical, but also spiritual, where faith and knowledge become the light that guides humans out of the darkness of ignorance and misguidance. In terms of mysticism, this tafsir describes how humans can achieve closeness to God through an esoteric understanding of the Qur'an. Thus, this study shows that Tafsir Al-Mizan integrates rational and mystical approaches in understanding the spiritual meaning of the Qur'an.